Critical Thinking in the Workplace - Jereb, Eva; Urh, Marko (Sodobni pristopi v kadrovskem managementu in izobraževanju, 2026)
The rapid development of technology is changing the knowledge and skill requirements for work. With the introduction of automation and artificial intelligence, workplaces are undergoing significant changes. Specific employee skills will become obsolete over time. However, there will be a need for other knowledge and skills. One of which is undoubtedly critical thinking. The chapter first presents what critical thinking is and what it is not. Next, the skills necessary for critical thinking and possible obstacles that make it more difficult are defined. Ultimately, Paul-Elder's concept of critical thinking is presented, enabling employees to work more efficiently and make informed decisions.